Design, Development, and Evaluation of DivTCell App: Gamifying Eukaryotic Cell Division and its Effects on Academic Achievement - S. A. A. Mantilla; L. A. Macababat; R. D. S. Nasayao; A. M. P. Walag (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
Due to the increasing popularity of digital games, educators worldwide have grown interested in designing and developing gamified learning systems to facilitate learning. The study utilized a design and development research design to develop a gamified learning app, DivTCell, to teach eukaryotic cell division to high school students. The application was designed based on suggestions from science teachers and emerging themes in the literature. It was then evaluated by science teachers using an application evaluation rubric. The DivTCell was implemented in one in-tact class to examine its effects in improving students’ academic achievement. Results from the evaluation show that the application have accurate concepts, accessible, and functional. Similarly, improvements in academic achievement were also noted after the implementation of the app as shown in the significant difference in the scores for the pretest (M=26.80, SD=2.32) and posttest (M=30.76, SD=2.44) conditions; t(45)= -8.49, p = 0.00. Effect size was also calculated at d=1.25, indicating high practical significance. Game elements such as badges, leaderboards, challenges, and autonomy are essential in motivating students to learn. These results demonstrate that when end users are in mind in developing a gamified learning system that positively affects students’ academic achievement.